The Importance of Indonesian Language Courses in Preventing the Negative Influence of Slang among University Students - Widia Nurhalimah Tarigan; Nur Hakima Akhirani Nasution; Ulfah Mayanti Hasibuan; Taufik Faizal (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Indonesian language plays an essential role in shaping students’ logical, critical, and scientific thinking skills. However, the rapid growth of technology and social media has led to the widespread use of slang among students, which may reduce their awareness of using formal language in academic contexts. This study employs a literature review method to examine the role of the Indonesian Language course in preventing the negative influence of slang on students’ formal language proficiency. The findings reveal that the course serves as a medium for developing academic ethics, sociolinguistic awareness, and intellectual identity. Through digital literacy–based learning and contextual language understanding, students are expected to use language appropriately according to context, thereby maintaining linguistic values and national identity in the globalization era.